PENGARUH CAPITAL INTENSITY,KOMITE AUDIT,KONSERVATISME AKUNTANSI TERHADAP TAX AVOIDANCE - Rila Darma Pangesti, Ni Putu Ayu; Ratnaningsih, Stephana Dyah Ayu (FEB Universitas Sam Ratulangi Manado, 2023)
This study is targeted at explaining the impact of Capital Intensity, Audit Committee and Accounting Conservatism on Tax Avoidance. This assessment uses a quantitative method and contains secondary data that can be obtained from annual information and sustainability reports issued by each company. This study has a population of all mining sector manufacturing companies verified on the IDX. From the entire population, the sample was selected using purposive sampling. The hypothesis was tested using multiple linear regression. The results of the study show that Capital Intensity has a significant impact on Tax Avoidance, the Audit Committee does not have a significant impact on Tax Avoidance, and Accounting Conservatism has a significant impact on Tax Avoidance